Fixed points and dynamic programming in complex-valued controlled metric spaces - GURAN, Liliana; SUHAIL ASLAM, Muhammad; RAHIM CHOWDHURY, Mohammad Showkat; ABDELJAWAD, Thabet (Studia Universitatis Babeș-Bolyai Mathematica, 2026)
In this paper, we introduce the concepts of (α − Θ)-contraction and Reich-type contraction within the framework of complex-valued controlled metric spaces (CVCMS). We also present related fixed point theorems for CVCMS, building on the works considered in the literature review for controlled metric type spaces. To demonstrate the practical implications and significance of our results, we provide several examples and an application in dynamic programming. Mathematics Subject Classification (2010): 47H10, 54H25. Received 09 September 2025; Accepted 03 February 2026.